A diffusion of innovations measurement scale for reinvention, relative advantage, compatibility, complexity, trialability and observability - Hannah Overbye-Thompson; Kristy A. Hamilton (PLoS ONE, 2025)
Diffusion of innovations (DOI) theory identifies critical factors that influence technology adoption rates and offers a predictive model for understanding how innovations spread through populations. While DOI theory encompasses six key perceptual characteristics (relative advantage, compatibility, complexity, trialability, observability, and reinvention), most empirical research operationalizes only Rogers’ five core attributes, rarely integrating reinvention despite its theoretical importance for understanding post-adoption adaptation. This research develops and validates a comprehensive scale measuring all six DOI characteristics, with particular attention to the reinvention construct. Through three independent samples (n = 2,019), we test the scale’s validity within a nomological network, creating an adaptable instrument for studying innovation diffusion that captures the full scope of DOI theory.